Analysis of The Influence of Integrated System Development, Accounting Technological Updates and Management Support on Accounting Information System Performance - Rasyid, Abdul; Ariani, Dian; Kusumaningati, Iip Dyah; Indriadewi Atmadjaja, Yovita Vivianty; Mertha Agung Durya, Ngurah Pandji (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to investigate how the performance of accounting information systems is affected by advancements in technology, support from upper management, education and training, and formalization of system development. This kind of investigation is called a causal study. This study employed primary data for its analysis. A questionnaire is the method used in this study to collect data. Retail companies make up the research's population. In this study, convenience sampling techniques are combined with non-probability sampling to pick the sample. Multiple linear regressions are used in this study's testing. The study's conclusions revealed a number of significant things about the variables affecting how well accounting information systems function in businesses. First, the performance of AIS is negatively impacted by technical advancements. This is a result of the usage of increasingly sophisticated technology, which calls for a higher level of comprehension and expertise to handle. Second, AIS performance is positively impacted by senior management support. Top management may provide strong oversight and support to enable AIS users to work more productively and strategically toward company objectives. Additionally, AIS development can proceed as planned to yield timely and correct information. Third, there is no benefit to AIS performance from user education and training. This is brought on by a dearth of resources and funding for users to engage in training and education. Lastly, the performance of AIS is improved by the formalization of system development. Formalizing system development will make it easier for AIS users to comprehend and operate the system in accordance with accepted standards, enabling them to generate accurate, timely, and trustworthy information that will enhance AIS performance as a whole.